2008
DOI: 10.1163/156856208784613523
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ether imide) membranes: studies on the effect of surface modification and protein pre-adsorption on endothelial cell adhesion, growth and function

Abstract: Surface modifications of poly(ether imide) (PEI) membranes with carboxylic groups were tested in comparison to pure PEI and poly(ethylene terephtalate) (PET) for their ability to support attachment, growth and function of human umbilical vein endothelial cells (HUVEC) in respect to endothelization of the above materials. Flat sheet PEI membranes were modified by covalent binding of iminodiacetic acid (IDA) for different periods of time (1 to 30 min) to obtain surfaces with various content of carboxylic grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…Tzoneva et al reported that human umbilical venous endothelial cells (HUVEC) were able to adhere and proliferate on PEI-membranes. 37 In a comparative study between PEI-membranes and -films, Braune et al showed that platelet adherence can strongly be reduced by the processing of PEI (by changing surface roughness). 6 Therefore, this study was performed to investigate the behavior of HUVEC seeded on smooth PEIfilms (R q = 2.37 ± 1.40 nm).…”
Section: Viability and Function Of Primary Human Endothelial Cells Onmentioning
confidence: 99%
“…Tzoneva et al reported that human umbilical venous endothelial cells (HUVEC) were able to adhere and proliferate on PEI-membranes. 37 In a comparative study between PEI-membranes and -films, Braune et al showed that platelet adherence can strongly be reduced by the processing of PEI (by changing surface roughness). 6 Therefore, this study was performed to investigate the behavior of HUVEC seeded on smooth PEIfilms (R q = 2.37 ± 1.40 nm).…”
Section: Viability and Function Of Primary Human Endothelial Cells Onmentioning
confidence: 99%
“…PEI is non-toxic, sterilizable [1], processable to different formed-bodies [4,5], and enables a wide range of surface modifications by straightforward wet chemistry [2, 3] and was already evaluated as a biomaterial [6,24,32,35,36] suitable for applications in regenerative medicine [30,41].…”
mentioning
confidence: 99%
“…A simple route to tailor PEI surface properties, for example by grafting of functional groups, allows for the adaptation of surface properties to the respective application demands (Braune et al ., ; Neffe et al ., ; Seifert et al ., ; Tzoneva et al ., ), while very good membrane‐forming properties have also been reported for PEI (Kneifel and Peinemann, ; Peinemann et al ., ). With regard to biocompatibility, PEI materials exert minimal cytotoxicity, good haemocompatibility (Imai et al ., ; Richardson et al ., ; Rüder et al ., ; Schulz et al ., ; Tzoneva et al ., ), are immunocompatible (Roch et al ., ) and allow for the attachment and growth of different cell types (Kawakami et al ., ; Kim et al ., ; Schneider et al ., ; Schulz et al ., ; Tzoneva et al ., ). On the basis of these results, PEI membranes have emerged as suitable materials for blood‐contacting applications, such as blood detoxification and oxygenation (Kawakami et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Although PEI has shown great promise for biomedical applications through numerous in vitro studies, especially with vascular cells (Kim et al ., ; Lange et al ., ; Roch et al ., ; Schulz et al ., ; Tzoneva et al ., ) and initial in vivo biocompatibility tests of PEI bulk samples (Peluso et al ., ), the impact of basic material topography on the implant reaction has not yet been investigated. In an effort to expand the previously made observations, we investigated the biocompatibility of two basic forms of material morphology in a physiologically relevant in vivo model.…”
Section: Introductionmentioning
confidence: 99%